Study Literature: The Influence of STEAM Learning on Student’s Literacy-Numeracy Ability (PRISMA, Prosiding Seminar Nasional Matematika, 2023)
Literacy-numeracy ability is one of the competencies that is closely related to human activities in daily life in the Society 5.0 era. Based on the 2019 PISA survey, Indonesian literacy is ranked 62 out of 70 countries. From these data, it can be shown that Indonesian literacy is still very low. This study aims to determine the effect of learning that is integrated with STEAM (Science, Technology, Engineering, Art, and Mathematics) on the literacy-numeracy ability of Indonesian students which are considered to be lacking. The method used is a literature study by taking data from previous studies to answer the influence of STEAM learning on students' literacy-numeracy ability. By applying STEAM-based learning that involves literacy-numeracy activities, it turns out to have an effect on students' literacy-numeracy ability as shown by the comparison of student learning outcomes from before and after learning the STEAM model. Further research is needed regarding more varied STEAM learning innovations so that maximum learning outcomes are obtained.